EDUCATIONAL WORK IN TEACHER EDUCATION: reflections from Supervised Internship - Temoteo, Paulo Antonio de Oliveira (2023)
The aim of this article is to report and analyze the educational work carried out in a state school in the south of Minas Gerais, as part of the Supervised Internship in a Biological Sciences course. We consider "work" to be the vital activity of human beings, through which men and women transform nature and themselves. We used qualitative research as the basis for our investigation, with reports based on participant observation, taking the experiences lived as the object of study. Supported by Historical-Critical Pedagogy and critical approaches to Supervised Internship in teacher training, we observed and discussed important elements for understanding educational work: the conditions of teaching work; pedagogical practices in the classroom and some of their obstacles; observations of the environment beyond the classroom; a vegetable garden project developed at the school; reflections on the individualization of responsibilities and the challenges for pedagogical practices; and, finally, the Pedagogical Political Project and its articulation with educational work. Based on these discussions, we understand and defend the Supervised Internship as a powerful activity for experiencing and reflecting on educational work, an important moment for building identity, valuing and training teachers as critical intellectuals.